2005
DOI: 10.1097/01.smj.0000129925.70634.53
|View full text |Cite
|
Sign up to set email alerts
|

Female Patientsʼ Sex Preferences in Selection of Gynecologists and Surgeons

Abstract: Our investigation demonstrated that women's preferences for a gynecologist were divided equally between preferring a male, a female, and having no preference. Our study did find, however, that about half of the female patients preferred a male surgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…Practice data from the USA showed that female urologists take on a higher workload for urogynecological procedures than their male colleagues 12 . This pattern has also been seen in general practice and obstetrics 21,22 . Female patients prefer a female doctor for sensitive interactions, such as breast examination and cervical screening 23 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Practice data from the USA showed that female urologists take on a higher workload for urogynecological procedures than their male colleagues 12 . This pattern has also been seen in general practice and obstetrics 21,22 . Female patients prefer a female doctor for sensitive interactions, such as breast examination and cervical screening 23 .…”
Section: Discussionmentioning
confidence: 92%
“…For some patients in the present study, previous healthcare interactions influenced their current gender preference. It has been reported that women are more likely to prefer a male obstetrician if their previous obstetrician was male and they had had a positive interaction 22 …”
Section: Discussionmentioning
confidence: 99%
“…Only one other study examined this issue and found that most women would stop douching if a HCP told them that doing so could increase their susceptibility to STIs, infertility, or cancer. 36 Given the fact that many girls reach menarche and begin douching prior to their first gynecological visit, pediatricians may be in the best position to first address douching, 45,46 especially since the best model of stopping this practice may be to prevent it from the beginning.…”
Section: Discussionmentioning
confidence: 99%
“…The gender of a surgeon has a significant bearing on the patients' preference in situations in which health concerns are intimate, or gender related. Various studies have been conducted on patients undergoing urological procedures, 1 gynecological surgeries, 4 breast reconstruction, 5 and gender affirmation surgeries 2 to analyze whether significant gender preference exists among patients when choosing the treating surgeon. Some studies have also shown that female patients are known to prefer female surgeons, while male patients prefer male surgeons.…”
Section: Discussionmentioning
confidence: 99%